2017
DOI: 10.1080/15384101.2016.1252881
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PPAR transcription factors in the energetic metabolic switch occurring during adult neurogenesis

Abstract: PPARs are a class of ligand-activated transcription factors belonging to the superfamily of receptors for steroid and thyroid hormones, retinoids and vitamin D that control the expression of a large number of genes involved in lipid and carbohydrate metabolism and in the regulation of cell proliferation, differentiation and death. The role of PPARs in the CNS has been primarily associated with lipid and glucose metabolism; however, these receptors are also implicated in neural cell differentiation and death, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…Parkinson disease is the second most common neurodegenerative disorder and pathologically characterized by selective loss of dopaminergic neurons in SNpc of the midbrain. The underlying precise mechanisms remain unclear, but the transcriptional factors are recognized to be important contributing factors in the neuron metabolism and maintenance of normal intracellular homeostasis . The bHLH proteins, a superfamily of transcription factors, play an important role in the development and regeneration of the nervous system .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson disease is the second most common neurodegenerative disorder and pathologically characterized by selective loss of dopaminergic neurons in SNpc of the midbrain. The underlying precise mechanisms remain unclear, but the transcriptional factors are recognized to be important contributing factors in the neuron metabolism and maintenance of normal intracellular homeostasis . The bHLH proteins, a superfamily of transcription factors, play an important role in the development and regeneration of the nervous system .…”
Section: Discussionmentioning
confidence: 99%
“…*P<.05, **P<.01, ***P<.001 vs. control (PBS), # P<.05, ### P<.001 vs. MPP + treatment mechanisms remain unclear, but the transcriptional factors are recognized to be important contributing factors in the neuron metabolism and maintenance of normal intracellular homeostasis. [43][44][45] The bHLH proteins, a superfamily of transcription factors, play an important role in the development and regeneration of the nervous system. 46 Many of bHLH proteins have been implicated in the differentiation and maintenance of mesencephalic dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…About 40% of PD patients are affected with cognitive impairment and dementia, which are about 6 times more frequent in PD patient comparing to healthy, age related control people. Several previous studies indicated promising effects of PPAR agonists in PD [95][96][97][98]. Previously also Carta et al [99] reported ameliorating effect of rosiglitazone which decreased PPAR-γ level and inhibited TNFα production in progressive PD mice model.…”
Section: Ppar-α Natural and Synthetic Agonists: From Experiments To Cmentioning
confidence: 92%
“…In contrast, a recent study from our group highlighted that the selective CB2 receptor agonist JWH133 specifically counteracted the chronic ethanol exposure-induced impairment of NSPC proliferation and maturation in the main neurogenic niches of the adult rat brain (Rivera et al, 2015b). PPAR isoforms can directly regulate neuronal cell proliferation, survival and differentiation (Cimini and Ceru, 2008;Di Giacomo et al, 2017). Specifically, PPARα can be implicated in the progressive age-associated decline of NSPC proliferation (2, 6 and 18 months), an effect that was partially compensated in enriched environments when PPARα is lacking (Pérez-Martín et al, 2016).…”
Section: Discussionmentioning
confidence: 99%